2006
DOI: 10.1128/aem.00601-06
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Geographic Isolation and Signs of Endemism within a Protistan Morphospecies

Abstract: The possible existence of endemism among microorganisms resulting from and preserved by geographic isolation is one of the most controversial topics in microbial ecology. We isolated 31 strains of "Spumella-like" flagellates from remote sampling sites from all continents, including Antarctica. These and another 23 isolates from a former study were characterized morphologically and by small-subunit rRNA gene sequence analysis and tested for the maximum temperature tolerance. Only a minority of the Spumella morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…Although we acknowledge that our dataset represents only a crosssection of the biodiversity of east Antarctic lakes, both eukaryotic and cyanobacterial communities are structured by geographical factors, after environmental variables are factored out. This, together with the relatively high amount of cyanobacterial sequences that have no relatives from non-Antarctic environments in GenBank, and the presence of Antarctic endemics in at least 3 other taxonomic groups, namely diatoms , flagellates (Boenigk et al 2006) and green algae (De Wever et al 2009), appears to contradict previous claims that for microorganisms "everything is everywhere" (Baas Becking 1934). Our results thus suggest that Antarctic microbial communities are probably structured by the same processes as those occurring in macroorganisms, as has been observed in studies of global diatom communities (Vyverman et al 2007).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although we acknowledge that our dataset represents only a crosssection of the biodiversity of east Antarctic lakes, both eukaryotic and cyanobacterial communities are structured by geographical factors, after environmental variables are factored out. This, together with the relatively high amount of cyanobacterial sequences that have no relatives from non-Antarctic environments in GenBank, and the presence of Antarctic endemics in at least 3 other taxonomic groups, namely diatoms , flagellates (Boenigk et al 2006) and green algae (De Wever et al 2009), appears to contradict previous claims that for microorganisms "everything is everywhere" (Baas Becking 1934). Our results thus suggest that Antarctic microbial communities are probably structured by the same processes as those occurring in macroorganisms, as has been observed in studies of global diatom communities (Vyverman et al 2007).…”
Section: Discussionmentioning
confidence: 69%
“…This is likely due to the fact that the SSU rDNA is insufficient to discriminate to the species level because of its low taxonomic resolution. In fact, previous studies reported a relatively high number of endemics belonging to a variety of eukaryotic taxonomic groups (Barnes et al 2006, Gibson et al 2006b), such as diatoms , Esposito et al 2006, nematodes (Bamforth et al 2005), ciliates (Petz et al 2007), mites and springtails (Convey & Stevens 2007), flagellates (Boenigk et al 2006) and recently also green algae (De Wever et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The debate over the degree to which protist communities exhibit global distribution has not been fully resolved (Foissner, 1999(Foissner, , 2006Lawley et al, 2004;Boenigk et al, 2006;Bass et al, 2007;Caron, 2009). We would like to emphasize that all existing knowledge of microbial diversity comes from samples, and, strictly speaking, is limited to the collection of samples analyzed so far-rather than environments from which they were obtained.…”
Section: Total Protistan Richness In the Cariaco Basinmentioning
confidence: 99%
“…Geographic isolation may also be responsible for the diversification of eukaryotic groups during the Cryogenian. Several recent studies have documented evidence of geographic isolation and divergence in modern protist groups (Boenigk et al 2006;Foissner et al 2007;Casteleyn et al 2010), suggesting that protists in modern ecosystems are not cosmopolitan. As such, global glaciation may have potentially stimulated diversification, while keeping overall abundance low.…”
Section: Diversity Patterns In Relation To Tectonic and Geochemical Fmentioning
confidence: 99%